2014
DOI: 10.17221/7623-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic ACTH syndrome in a dog with a mesenteric neuroendocrine tumour: a case report

Abstract: Ectopic ACTH secretion is provoked by extra-pituitary tumours that secrete ACTH, constituting an infrequent type of Cushing Syndrome in the dog. Neuroendocrine tumours (NET) are characterised by the synthesis of peptides with hormone activity. A dog with clinical diagnosis of Cushing's syndrome and presenting an abdominal tumour located in the area of the left adrenal gland was sent to the hospital. Cortisol was not inhibited at four and eight hours after the application of low-dose dexamethasone and the corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Ectopic Cushing's syndrome accounts for approximately 5% of all human cases of Cushing's syndrome [3]. Primary hepatic carcinoid and neuroendocrine tumors are reportedly related to ECS; however, to the authors' knowledge, canine ECS related to pheochromocytoma has not been previously reported [4][5][6]. In the present case study, we describe ECS caused by pheochromocytoma in a dog.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Ectopic Cushing's syndrome accounts for approximately 5% of all human cases of Cushing's syndrome [3]. Primary hepatic carcinoid and neuroendocrine tumors are reportedly related to ECS; however, to the authors' knowledge, canine ECS related to pheochromocytoma has not been previously reported [4][5][6]. In the present case study, we describe ECS caused by pheochromocytoma in a dog.…”
Section: Introductionmentioning
confidence: 71%
“…Ectopic production of CRH and ACTH has been reported infrequently in humans and rarely in dogs. To the authors' knowledge, ECS caused by pheochromocytoma in dogs has not been previously reported, although previous case reports involving canines with mesenteric neuroendocrine tumors and a primary hepatic carcinoid suggested that the tumors were related to ECS [4][5][6]. A case involving a 5-year-old male Dachshund with Cushing's syndrome was reportedly due to ectopic secretion of ACTH by an unidentified microadenoma.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…NETs are rarely functional in animals to secrete hormones, including glucagon and serotonin, leading to hormone-associated diseases [1,3,17,20]. As far as we known, adrenocorticotropic hormone (ACTH)-producing NET has been only reported in one dog [3]. The present report describes the computed tomographical, histopathological, and immunohistochemical findings of ACTH-producing NET found in the sinusoidal cavity and brain in an 18-year-old dog in association with Cushing's disease.…”
mentioning
confidence: 84%
“…As the clinical, histopathological, and immunohistological characteristics of these tumors, particularly in the nasal cavities and brain, are similar to other tumors, such as olfactory neuroblastomas, differential diagnosis is usually required [24]. NETs are rarely functional in animals to secrete hormones, including glucagon and serotonin, leading to hormone-associated diseases [1,3,17,20]. As far as we known, adrenocorticotropic hormone (ACTH)-producing NET has been only reported in one dog [3].…”
mentioning
confidence: 99%